Ecosystem accounting of forests in sustainable environmental management: basic content and development - Bahedh, Hayder; Yatsukhno, Valentin (Journal of the Belarusian State University. Ecology, 2024)
The presented article examines the topical issues of the formation of ecosystem accounting of forests in the context of the formation and development of environmental and economic accounting. Numerous scientific works by both Belarusian and foreign scientists are devoted to this problem. However, ecosystem accounting of forests, from the formative environmental accounting, is not fully investigated. In this paper, an attempt is made to define the conceptual and methodological foundations for building ecosystem accounting of forests as a function of forest management and a structural element of system national accounting (SNA). It is important to pay attention to the authors’ arguments regarding the consideration of the content and distinctive features of environmental accounting, the object of which is environmental capital and ecosystem services. The difference between economic and environmental accounting is of fundamental importance for the separate expression of the value of natural resources using in different spheres and as well as dynamics of vital and irreplaceable ecosystem services and, in general, environmental capital. The construction of generalized accounts of ecosystem services based on the principles of the system environmental and economical accounting (SEEA) [1]. The authors propose a method of physical and cost accounting of forests. The main carrier of ecosystem services of forests is the wood stock and its dynamics over time and the cost measurement is based on environmental rent. This methodological approach is based on the theory of reproductive rent and has its practical output in the ТСР 17.02-10-2013(02120) “Procedure for conducting valuation, ecosystem services and determining the value of biological diversity” developed under the scientific guidance of prof. A.V. Neverov.